Uncertainty appraisal coping and quality of life in breast cancer survivors - Tipaporn Wonghongkul (2018)
Breast cancer survivors increasingly experience long-term side effects that influence their quality of life. They also experience uncertainty of their future due to recurrence of disease. Descriptive design was conducted. Using convenience sampling, 150 breast cancer survivors of more than 3 years from time of diagnosis were recruited from Maharaj Nakorn Chiang Mai Hospital, Chiang Mai, Thailand. Research instruments included Mishel Uncertainty in Illness Scale, Stress Appraisal Index, Ways of Coping Questionnaire, and Quality of Life: Breast Cancer Version Questionnaire and Demographic Data Questionnaire. Results revealed that breast cancer survivors had moderate levels of uncertainty in their illness. Survivors appraised their illness and found high level of challenges, moderate level of threat, and low level of harm. Overall quality of life was found to be moderate. Among Ways of Coping strategies, seeking social support was used the most and confrontive coping was used the least. Using hierarchical multiple regression, variables influencing quality of life were year of survival, uncertainty in illness, and harm appraisal. All 3 variables explained 21.8% variance of quality of life.Uncertainty and harm appraisal influence quality of life in breast cancer survivors. Suggestions and further implications were included. © 2006 Lippincott Williams & Wilkins, Inc.